Analisis Penetapan Harga Jual dengan Menggunakan Metode Cost Plus Pricing pada Cv. Wana Bhakti - Ok A Maulana Ibrahim; Alistraja Dison Silalahi (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study was to determine the selling price of the product based on the Cost Plus Pricing method. This research was conducted on CV. Wana Bhakti which is located on Jln. Kualanamu airport artery, market 5, GG. Education, Telga Sari village, Kec. Tanjung Morawa, Kab. Deli Serdang, North Sumatra Province. This study uses qualitative research methods to analyze data that aims to determine the results of the analysis of selling price determination using the cost plus pricing method on CV. Wana Bhakti. The subject of this research is CV. Wana Bhakti and the object of this research are the record of the production costs of durian and mango seeds in 2020 and the report on the cost of production of durian and mango seeds by company. CV. Wana Bhakti determines the selling price based on the company's calculations and adjusts the average market price without knowing whether the selling price has been set correctly or not to generate maximum profit. The results of this study indicate that there is a difference in the selling price determined by the company using the cost plus pricing method, namely the durian seeds Rp. 530 and sweet fragrant mango seeds Rp. 800 more expensive than the company's selling price. So that it can be taken into consideration by companies in setting prices.